Rancang Bangun Sistem Informasi Kegiatan Remaja Masjid (KORMA) Berbasis Laravel Filament dengan Fitur Usulan Kegiatan Anggota dan Pengelolaan Keuangan - M.Syarifudin; Budi Jejen Zaelani Abidin; Miri Ardiansyah (JIKOMTI : Jurnal Ilmiah Ilmu Komputer dan Teknologi Informasi, 2026)
Mosque youth organizations play a significant role in supporting various religious, social, and community activities. However, activity management and financial administration are still carried out conventionally, causing problems such as low efficiency, lack of transparency, and difficulties in decision-making. This study aims to design a web-based information system for mosque youth activities (KORMA) using the Laravel Filament framework, integrated with activity and financial management. The system also implements the Simple Additive Weighting (SAW) method to assist in determining activity priorities based on several criteria, including time proximity, category, popularity, time suitability, and the quality of activity descriptions. The research methodology applied is system development with implementation and testing stages. The results of the study indicate that the system is able to improve efficiency in activity management, provide clear financial records, and generate objective activity priority rankings. The SAW method has proven to support decision-making in a structured and measurable manner. It is expected that this system can enhance the effectiveness and accountability of mosque youth organizations.